Is Banks' Profitability Affected by Monetary and Investment Freedom of the Economy? Nepalese Prospective - Arjun Kumar Dahal,; Prem Bahadur Budhathoki,; Sagar Pokhrel, (Interdisciplinary Journal of Management and Social Sciences, 2025)
This study tries to navigate the impact of total loan volume, net interest margin, non-interest income, number of branches of banks, and monetary and investment freedom on determining the profit of commercial banks in Nepal. It is based on secondary data from the World Bank and World Heritage Index, with 27 data points from 1998 to 2024. The co-integration test and fully modified least square method explore the long-run impact of independent variables on dependent variables. It is based on the causal correlational research design. It follows the positivist research philosophy and deductive reasoning. The co-integration analysis confirms the validity of long-run equilibrium relationships among the variables, thus pointing out their interrelationship and continuing influence on profitability. The profitability of Nepalese commercial banks is significantly positively influenced by total loan volume, non-interest revenue, net interest margin, and investment freedom. The profitability of Nepalese banks rises by 0.671, 0.061, and 0.737 percent for every one percent growth in total loan amount, non-interest income, and net interest margin, respectively. Similarly, bank profitability rises by 0.022 percent for every one percent increase in investment freedom. On the other hand, branch numbers adversely affect profitability, suggesting possible inefficiencies or financial strains associated with branch growth. The commercial banks' profit decreased by 0.654 percent with the one percent increase in branches of commercial banks. However, monetary freedom has not significantly impacted banks' earnings in Nepal. Policymakers and banking regulators should focus on enhancing loan portfolio management, optimizing net interest margins, promoting digital banking, ensuring efficient branch expansion, and aligning monetary policy reforms with broader economic goals to boost banking sector profitability.